Participation experiences of people with deafblindness or dual sensory loss: A scoping review of global deafblind literature. - Atul Jaiswal; Heather Aldersey; Walter Wittich; Mansha Mirza; Marcia Finlayson (PLoS ONE)
Background Deafblindness, also known as dual sensory loss, is a varying combination of visual and hearing impairment in the same individual. Interest in this topic has increased recently due to evidence suggesting an increase in prevalence of this condition among older adults. Persons with deafblindness frequently experience participation barriers and social isolation. Developing an understanding of their experiences can inform the design of programs and policies to enhance participation of people with deafblindness in society. Objective To identify and summarize available research literature on participation experiences of people with deafblindness or dual sensory loss. Methods A comprehensive literature search of eight databases (CINAHL/EBSCO, Embase, ERIC, Global Health, MEDLINE, ProQuest, PsycINFO, PubMed) was performed in accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA) during January 2017 and last updated in June 2017. In addition, non-peer reviewed (grey) literature was also retrieved in the form of online published reports of research projects by 16 deafblind-specific organizations across the globe. To be included, sources had to be published after 1990, had persons with deafblindness as the focal population, and focused on their participation experiences. Results A total 1172 sources were identified of which 54 studies were included. The findings reveal that persons with deafblindness, regardless of origin of their impairment, experience difficulty in communication, mobility, daily living functioning, and social interactions. While these experiences may vary between individuals with congenital versus acquired conditions, they generally feel socially isolated, insecure and uncertain about their future. Conclusion Participation experiences of persons with deafblindness are shaped by dynamic interactions between personal factors (such as onset and type of impairments) and environmental influences (such as attitude, technology, and supports). A better understanding of participation experiences may help professionals in placing emphasis on affected participation domains to design services to enhance participation of people with deafblindness.